2018
DOI: 10.1002/ajpa.23460
|View full text |Cite
|
Sign up to set email alerts
|

Bone functional adaptation does not erase neutral evolutionary information

Abstract: Among-population patterns of diaphyseal variation are consistent with neutral expectations and are consistent with historical data on population composition, genetics, and migration. Furthermore, plasticity induced by Industrial-era levels of physical activity does not erase these neutral signatures. Diaphyseal variation may therefore be useful to infer neutral (presumably genetic) information across populations, and controlling for existing relationships may strengthen inferences of physical activity made whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 160 publications
0
23
0
1
Order By: Relevance
“…In turn, the lower loads engendered by a smaller body or a genetic difference in bone cross‐sectional size could theoretically account for low cross‐sectional properties in this group. It is also possible that genetic differences directly contribute to differences in cross‐sectional properties (Agostini et al, 2018). More diachronic stability in skeletal phenotype among urban groups may indicate that either the genetic contribution of migrants was subsumed within a larger population or that urban and rural migrants had different origins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the lower loads engendered by a smaller body or a genetic difference in bone cross‐sectional size could theoretically account for low cross‐sectional properties in this group. It is also possible that genetic differences directly contribute to differences in cross‐sectional properties (Agostini et al, 2018). More diachronic stability in skeletal phenotype among urban groups may indicate that either the genetic contribution of migrants was subsumed within a larger population or that urban and rural migrants had different origins.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have repeatedly demonstrated that population structure explains a substantial portion of variation in body size between populations (Allen, 1877; Cowgill, Eleazer, Auerbach, Temple, & Okazaki, 2012; Holliday, 1997; Roseman & Auerbach, 2015; Ruff et al, 2012). Similarly, while patterning in bone cross‐sectional properties between groups predominantly reflects behavioral differences, it has also been shown to carry a neutral genetic signature (Agostini et al, 2018). As Ibiza has been repeatedly colonized throughout its history, the contribution of migration to Ibiza's genetic history makes this an especially important consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential that morphologists recognize the value of adopting a hierarchical approach to evolutionary hypothesis testing, starting with a falsifiable null model of neutral evolution and thereafter building more complex explanatory models that include the potential effects of selection, correlated evolution, and phenotypic plasticity. This is particularly salient in the case of postcranial skeletal traits, such as long bone morphology, that have traditionally been assumed to not follow a neutral model of divergence due to their functional importance . However, this assumption should first be explicitly tested as function‐induced plasticity does not automatically obscure the signature of past neutral divergence among groups …”
Section: Conceptual Stumbling Blocks In the Evolutionary Analysis Of mentioning
confidence: 99%
“…This is particularly salient in the case of postcranial skeletal traits, such as long bone morphology, that have traditionally been assumed to not follow a neutral model of divergence due to their functional importance . However, this assumption should first be explicitly tested as function‐induced plasticity does not automatically obscure the signature of past neutral divergence among groups …”
Section: Conceptual Stumbling Blocks In the Evolutionary Analysis Of mentioning
confidence: 99%
See 1 more Smart Citation